The PREY COMPOSITION OF Nepenthes gymnamphora Reinw. Ex Nees AT MOUNT BISMO, DERODUWUR HIKING TRAIL, WONOSOBO, CENTRAL JAVA - Hani Ristiawan; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Nepenthes gymnamphora (kantong semar, palaeotropic pitcher plant) is a carnivorous plant that spreads across the mountains of Java, one of which is on Mount Bismo, Dieng Mountains, Central Java. The prey composition N. gymnamphora here has not been studied before. The purpose of this study was to identify the composition of prey of N. gymnamphora in the Deroduwur Hiking Trail, Mount Bismo, Wonosobo, Central Java. The method used is the identification of prey in the pitcher that has been opened, both the upper and lower pitcher types. The main prey of N. gymnamphora are invertebrates from the ordo of Hymenoptera, Blattodea, Diptera, Araneae, and Diplura. Based on the prey composition analysis, there was a tendency of pitcher dimorphism, namely the upper pitcher of N. gymnamphora tended to contain flying invertebrates, while the lower pitcher tended to contain terrestrial invertebrates. This is influenced by the morphology of the pitcher, the upper pitcher tends to be lighter in color than the lower pitcher so that it is more attractive to fly invertebrates. In addition, the pitcher of N. gymnamphora provides a microhabitat for the larvae of Culicidae and Syrphidae. Keywords: carnivorous plants, Mount Bismo, Nepenthes gymnamphora, prey composition.